Translanguaging as a way to fostering EFL learners' criticality in a hybrid course design. (November 2022) - Yüzlü, Muhammet Yaşar; Dikilitaş, Kenan
Abstract: This case study examines the growth of criticality in three English as a Foreign Language (EFL) learners through a hybrid course design which involves a translanguaging space for the development of reading and listening skills. Throughout the course, the learners were encouraged to deal with multimodal materials presented both in Turkish and English in line with translanguaging pedagogy. They were guided to use their full linguistic repertoire in digitally enriched translanguaging space and critically analyze the reading materials in group discussions and reflective writing activities. An exploratory approach is adopted, based upon a series of interviews with EFL learners, observations of their contributions to face-to-face debate lessons, and their reflective papers. All three learners developed criticality to varying degrees. Having discussed the significance of translanguaging in the development of criticality, we introduce implications for the relationship between criticality, translanguaging, and technology for fostering criticality of EFL learners. Then, we present pedagogical implications for teachers and teacher educators as to how fuller understanding and deep learning can be engendered in asynchronous sessions, and how digiticality (digitally-enriched criticality) can be fostered by a hybrid translanguaging space. Implications from these findings may be used to inform classroom pedagogy.